Interview: Distance education policies and their legal guidelines evolution after 1990 to the current context - Dourado, Luiz Fernandes (2020)
In the present interview, by means of a dialogue established with teachers, also researchers and scholars on the subject, we propose a discussion on public policies of distance education and their legal guidelines evolution from the 1990s to the current context. As the dialogue develops, the legislation concerning Distance Education, the practices and the obstacles encountered are addressed. UAB, its benefits and limitations for teacher training, are also discussed. Special emphasis was given to professor Dourado’s experience as draftsman in the Commission for the Construction of the National Curriculum Guidelines for Distance Education in Higher Education Courses. Criticisms and reflections were added subsidies to the debate on the theme, especially in these times when we are experiencing a pandemic and that distance education, commonly used in an improvised way, has been requested to replace regular live classes. Finally, we see positive perspectives for the future of education, and distance education, in our country.